Comparative Analysis of Altman and Grover's Methods in Predicting Bankruptcy Using the McNemar Test (Case Study: Vehicle Insurance Company in Indonesia) - Siahaan, Roy Donald Pangeran; Rizqullah, Muhammad Rifan Marsa (International Journal of Quantitative Research and Modeling, 2024)
Vehicle insurance is an important component of automotive financing and consumer protection, which includes various forms of protection that protect the vehicle and its owner. Predicting the bankruptcy of a vehicle insurance company is also very important for vehicle insurance companies to be able to identify potential financial problems as early as possible and take the necessary corrective actions. The Altman and Grover model can be a way to analyze bankruptcy in company. In this study, PT. Asuransi Astra Buana, PT. Allianz Utama Indonesia, PT. Sinar Mas Insurance, and PT. BCA Insurance are used as the analyzed company. The McNemar Test conducted in this study shows that the two methods do not have significant differences in result, so the two methods will relatively have same results.